Safety of very high-power short-duration radiofrequency ablation for pulmonary vein isolation: a two-centre report with emphasis on silent oesophageal injury. Issue 3 (10th November 2021) - Halbfass, Philipp; Wielandts, Jean-Yves; Knecht, Sébastien; Le Polain de Waroux, Jean-Benoît; Tavernier, René; De Wilde, Vincent; Sonne, Kai; Nentwich, Karin; Ene, Elena; Berkovitz, Artur; Mueller, Julian; Lehmkuhl, Lukas; et al.
Abstract: Aims: Very high-power short-duration (vHPSD) via temperature-controlled ablation (TCA) is a new modality to perform radiofrequency pulmonary vein isolation (PVI), conceivably at the cost of a narrower safety margin towards the oesophagus. In this two-centre trial, we aimed to determine the safety of vHPSD-based PVI with specific emphasis on silent oesophageal injury. Methods and results: Ninety consecutive patients with atrial fibrillation (AF) underwent vHPSD-PVI (90 W, 3–4 s, TCA) using the QDOT MICRO catheter, in conjunction with the nGEN (Bad Neustadt, n = 45) or nMARQ generator (Bruges, n = 45). All patients underwent post-ablation oesophageal endoscopy. Procedural parameters and complications were recorded. A subgroup of 21 patients from Bad Neustadt underwent cerebral magnetic resonance imaging (cMRI) to detect silent cerebral events (SCEs). Mean age was 67 ± 9 years, 59% patients were male, and 66% patients had paroxysmal AF. Pulmonary vein isolation was obtained in all cases after 96 ± 29 min. No steam pop, cardiac tamponade, stroke, or fistula was reported. None of the 90 patients demonstrated oesophageal ulceration (0%). Charring was not observed in the nMARQ cohort (0% vs. 11% in the nGEN group). In 5 out of 21 patients (24%), cMRI demonstrated SCE (exclusively nGEN cohort). Conclusion: Temperature-controlled vHPSD catheter ablation allows straightforward PVI without evidence of oesophageal ulcerations or symptomatic complications. Catheter tip charring and silent cerebral lesions when using the nGEN generator have led to further modification.